Strategic Development Planning in the Perspectives of Public Accountability: Lesson from East Java in Indonesia - Puji Handayati; Eddy Sutadji; Bagus Shandy Narmaditya; Dwi Wulandari; Shadi Emad Areef Alhaleh; Putra Hilmi Prayitno (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2021)
This study is intended to identify the level of compatibility documents planning (RPJPD, RPJMD, and RKPD) between provincial and city/regency in East Java of Indonesia. In addition, this study also provides a framework in proposing documents for each city/regency in East Java. This research applied a qualitative method using content analysis. This study employed both primary and secondary data to gain a deeper understanding to the existing phenomenon. The primary data was gathered from in-depth interviews, while secondary data was achieved from several documents owned by each city/regency in East Java provincial. The findings of the study reveal that in general, the substance of the RPJMD in the twenty regencies/cities in East Java of Indonesia is in accordance with the provincial plan. However, there are several different sections of the format in the placement of chapters and sub-chapters of the naming of chapters. In the broader sense, the substance of the RKPD in the twenty regencies/cities is in accordance with the provincial plan.